23.9k views
4 votes
Please answer all please​

Please answer all please​-example-1
User Ben James
by
4.6k points

1 Answer

2 votes

Answer:

Explanation:

The first parabola has vertex (-1, 0) and y-intercept (0, 1).

We plug these values into the given vertex form equation of a parabola:

y - k = a(x - h)^2 becomes

y - 0 = a(x + 1)^2

Next, we subst. the coordinates of the y-intercept (0, 1) into the above, obtaining:

1 = a(0 + 1)^2, and from this we know that a = 1. Thus, the equation of the first parabola is

y = (x + 1)^2

Second parabola: We follow essentially the same approach. Identify the vertex and the two horizontal intercepts. They are:

vertex: (1, 4)

x-intercepts: (-1, 0) and (3, 0)

Subbing these values into y - k = a(x - h)^2, we obtain:

0 - 4 = a(3 - 1)^2, or

-4 = a(2)². This yields a = -1.

Then the desired equation of the parabola is

y - 4 = -(x - 1)^2

User Preetha
by
5.1k points